Access to improved water and sanitation: Key drivers for achieving Sustainable Development Goal 4 in Indian states - Priya Ranjan (Cleaner Water)
This study examines how access to improved water sources and sanitation facilities influences educational outcomes across Indian states and how these relationships support progress toward the Sustainable Development Goals (SDGs). Study using state-level data from secondary sources. States were classified into low, middle, and high categories for water, sanitation, and literacy based on percentile rankings for 2019–20 for comparing states' progress and identifying those lagging and successful states. Furthermore, correlation and linear multiple regression were employed in a cross-sectional framework to assess the relationship between variables. The findings reveal a substantial upward trend in access to both safe drinking water and improved sanitation over the past two decades. This progress has notably narrowed rural-urban disparities, yet significant regional inequities persist. The study shows that some states lack behind in access to basic clean water and sanitation facilities, such as Bihar, Jharkhand, Madhya Pradesh, and Odisha (especially in rural areas). The empirical results show a statistically significant positive relationship between access to improved sanitation facilities and literacy rates. It also shows a negative relationship with school dropout rates, particularly among girls. Improved water access is also linked to higher literacy and lower dropout rates. The study emphasizes the importance of integrated policy approaches in addressing educational and infrastructural deficits, particularly in vulnerable regions, for India's SDG commitments and inclusive, equitable development, including enhanced sanitation and safe water access.